Phoneme Elision in The meN- Prefix in The Jambi Malay of Bedaro Village - Ranti Permatasari; Lega Hidayati; Titiek Prihatiningsih (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2026)
This study examines morphophonemic formation, focusing primarily on phoneme elision that arises from the interaction between the bound morpheme meN- and certain free morphemes. The purpose is to describe the process of phoneme elision occurring in the meN- prefix in Jambi Malay as spoken by the community of Bedaro Village. The research focuses on morphophonemic forms that undergo phoneme elision as a result of the attachment of the bound morpheme meN- to specific free morphemes. A qualitative approach with a descriptive method was employed. The data consist of spoken utterances produced by native speakers of Jambi Malay in Bedaro Village and were collected using the listening method, supported by tapping, participant observation, recording, and note-taking techniques. The data were analyzed by identifying base forms and affixed forms to determine and classify instances of phoneme elision, which were then described based on linguistic principles. The findings indicate that phoneme elision in the Jambi Malay of Bedaro Village occurs when the meN- prefix attaches to free morphemes beginning with the consonants /c/, /s/, /k/, and /g/. In this process, the initial consonant of the base morpheme is deleted, resulting in a new phonological form. This study identified nine morphemes that undergo phoneme elision, including ukia, ŋato, ŋaji, ŋubua, ŋileŋ, and ŋulai. These findings demonstrate that phoneme elision in the meN- prefix follows systematic patterns and represents a distinctive morphophonemic feature of the Jambi Malay spoken in Bedaro Village.